2022
DOI: 10.1186/s12866-022-02696-7
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of virulence factors and carbapenemase genes in Salmonella enterica serovar Enteritidis isolated from chicken meat and egg samples in Iraq

Abstract: Background Food-borne infections mainly due to Salmonella enterica serovar Enteritidis (S. Enteritidis) are major concerns worldwide. S. Enteritidis isolates may serve as reservoirs for spreading antimicrobial drug resistance genes including carbapenemases. This study aimed to screen the occurrence of virulence factors, carbapenemases, and antibiotic resistance genes in S. Enteritidis isolated from chicken meat and eggs in Iraq. Results In total, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…In this study, the prevalence of resistance to amikacin and ciprofloxacin were considerably high. This results is consistent with previous studies on chicken meat conducted in Egypt and Iraq ( 27 , 28 ). The reporting of resistance to antibiotic agents in Salmonella isolates from fecal samples of chicken farms suggests the contamination and spread of resistant strains in the environment, posing a potential risk to both animals, humans, and public heaths.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, the prevalence of resistance to amikacin and ciprofloxacin were considerably high. This results is consistent with previous studies on chicken meat conducted in Egypt and Iraq ( 27 , 28 ). The reporting of resistance to antibiotic agents in Salmonella isolates from fecal samples of chicken farms suggests the contamination and spread of resistant strains in the environment, posing a potential risk to both animals, humans, and public heaths.…”
Section: Discussionsupporting
confidence: 93%
“…Also, Wang et al from China reported a high incidence of sopB (100%), and spvC (93.8%) among Salmonella serovars isolated from 120 retail meat samples ( 41 ). In studies in Iran and Nigeria the prevalence rates of spvC gene were 50.8%, 59.1%, and 45.8%, respectively ( 26 , 28 ). According to a study by Takaichi et al conducted in Indonesia, the prevalence rates of slyA, phoP/Q, and sopB were reported as 60%, 86%, and 88%, respectively ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this investigation tried to provide useful data to understand the connection between the utilization of antimicrobial agents in poultry production and the upsurge of the emergence of resistance in foodborne pathogens, such as Salmonella. The previous studies in Iraq confirmed this relationship by investigating the MDR phenomenon in many foodborne pathogens [21,[48][49][50][51]. Other studies in Iraq also pointed to wrong practices regarding the abuse and misuse of antibiotics, which drove the exacerbation of this phenomenon [52][53][54].…”
Section: Discussionmentioning
confidence: 73%
“…Salmonella has long been linked to poultry and related products [ 21 ]. In recent years, there has been widespread reporting of the growing prevalence of Salmonella and antimicrobial resistance (AMR) in food [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation